Analisis Kelongsoran Lereng Akibat Pengaruh Tekanan Air Pori di Saluran Induk Kalibawang Kulonprogo - Hesti Subiyanti; Ahmad Rifa’i; Rachmad Jayadi (Universitas Muhammadiyah Yogyakarta, 2011)
During rainy seasons, landslide occurs every year in Talang Bawong, Kalibawang Irrigation Channel thatcan damage houses, school building, bridge and the channel. Considering this fact, a numerical analysis by modeling the slope at the site was conducted. The objectives of this research were to identify the rain characteristic in the research site and to recognize its influence towards the change of water pressure in soil as well as the slope failure. The input data of this analysis were slope topography, physical and mechanical properties of soil applied. Groundwater flow in the slope model was numerically simulated by using SEEP/W software. Designed rainfall with appropriate return period was determined by analizing the maximum daily rainfall data with the aid of HAVARA software, while rainfall depth distribution was completed by applying frequency analysis. The historical daily rainfall data (1985 – 2004) were obtained from Kalibawang rain stasiun. Six rainfall models, as follow: initial condition (no rain) (model I), heavy rain in a short duration (model II), normal rain 25 mm and 40 mm in a long duration (model III), normal rain 20 mm in a long duration (model IV), heavy rain followed by normal rain 20 mm (model V), and normal rain 20 mm followed by heavy rain (model VI) Were analyzed. The output of the simulation was water pressure distribution data, which in turn being used as input data in analyzing slope stability using the SLOPE/W software. The result of the research showed that the highest rainfall with 2-year-return period was 114 mm while the dominant duration was 4 hours/day, and it was applied in the model II. The result showed that, a normal rain in a long duration is more severely influenced the change in water pressure than a heavy rain in a short duration. The safety factors are 1,444 for no rain condition, 1,418 for 114 mm rain for 4 hours, 1,208 for 25 mm and 40 mm rains, 0,982 for 20 mm rain, 1,397 for heavy rain followed by normal rain, and 1,402 for normal rain followed by heavy rain. In addition, a 20 mm normal rain on the 61st day resulted in the most severe influence on the slope failure.